The Efficacy of Washed Microbiota Transplantation on Helicobacter pylori Eradication: A Pilot Study. (20th October 2020) - Ye, Zhi-Ning; Xia, Harry Hua-Xiang; Zhang, Ran; Li, Lan; Wu, Li-Hao; Liu, Xu-Juan; Xie, Wen-Rui; He, Xing-Xiang
Abstract : Aim . The fecal microbiota transplantation by washed preparation was recently coined as washed microbiota transplantation (WMT). This pilot study is aimed at exploring the feasibility and efficacy of WMT on Helicobacter pylori eradication. Methods . Consecutive patients who had been treated with WMT for various indications and who were positive for H. pylori infection before WMT treatment but had never received eradication therapy for H. pylori infection were invited to take a follow-up 13 C-urea breath test. The associations of demographic, clinical factors, and laboratory indicators for gastric function and intestinal barrier function with the therapeutic effect were determined. Results . A total of 32 eligible patients were included, and the overall H. pylori eradication rate was 40.6% (13/32). Patients with H. pylori eradication had a higher pepsinogen ratio (PGR) than those without (13.00 ± 6.97 vs. 8.31 ± 3.733 ; P = 0.02 ). Female patients had a higher, albeit not statistically significant, eradication rate than male patients (53.85% vs. 31.58%; P = 0.208 ). Compared with lower gastrointestinal tract delivery route, middle gastrointestinal tract delivery route seems to be a more suitable way for the treatment of H. pylori infection (58.33% vs 16.67%; P = 0.152 ). There was no significant difference in other demographic and clinical factors between patients with and without H. pylori eradication. Conclusion . H. pylori infection is eradicated in a proportion of patients who have received WMT. An increased pre-WMT PGR appears to be associated with the therapeutic effect. Further studies are required to confirm the efficacy of WMT, especially in combination with currently recommended regimens in randomized controlled trials.